2018
DOI: 10.1016/j.msard.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Muscle carnosine in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: Muscle carnosine concentrations in an animal MS model and MS patients are substantially reduced. In EAE exercise therapy does not restore this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(97 reference statements)
0
13
1
Order By: Relevance
“…Previous studies on the effects of ET on EAE yielded variable results. Clinical outcomes ranged from worsening of symptoms, no effect on clinical severity, to disease attenuation, as indicated by delayed onset and peak of disease and even overall attenuation of the clinical course . The inconsistencies in these studies likely derived from variations in training modes (running, swimming) and protocols (intensity, speed, volume, duration) that were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of ET on EAE yielded variable results. Clinical outcomes ranged from worsening of symptoms, no effect on clinical severity, to disease attenuation, as indicated by delayed onset and peak of disease and even overall attenuation of the clinical course . The inconsistencies in these studies likely derived from variations in training modes (running, swimming) and protocols (intensity, speed, volume, duration) that were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Forced treadmill exercise paradigm has been used on EAE animals with conflicting results regarding the clinical score. Therefore, worsening of symptoms ( 24 ), no effect on disability ( 25 27 ), delayed day of peak disease ( 28 ) or of onset of disease ( 29 ) and even a global amelioration of clinical signs ( 30 , 31 ) has been demonstrated on EAE animals that have been exercised on treadmill. Nevertheless, different EAE models, as well as different volume, intensity and duration of exercise, may affect final conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic autoimmune and inflammatory disease of the CNS with progressive demyelinization [93]. In an animal model of multiple sclerosis, muscle carnosine levels were decreased and were not restored by exercise, which possibly mirrors altered muscular functions in MS [94]. Another animal study reported delayed onset of symptoms in exercising rats following the induction of MS [95].…”
Section: Animal Studies Of the Role Of Carnosine In Brain-related mentioning
confidence: 99%
“…Patients with multiple sclerosis have increased plasma histidine and decreased alanine levels compared with patients with other inflammatory demyelinating diseases [147]. Reductions in serum carnosinase activity have also been proposed as a potential explanation for the impaired exercise capacity, excessive post-exercise fatigue, and reduced muscle contractile function that are usually present in multiple sclerosis [94,148]. It is, therefore, not surprising that individuals with multiple sclerosis had reduced skeletal muscle carnosine content and 10-day exercise training did not restore it [94].…”
Section: Human Observational Studies Of the Role Of Carnosine In Bmentioning
confidence: 99%